The myth of the lazy lecturer : the academic-ability, industrial expertise and international competitiveness of Malaysian academics / Airil Haimi Mohd Adnan - Mohd Adnan, Airil Haimi (Unit for Research and Intellect Application (UfoRIA), 2009)
As Asian institutions of higher learning prepare to scale the heights of the Times Higher Education World Top Universities' list, academics in these institutions have been asked to actively collaborate in regional knowledge sharing initiatives and to foster stronger ties to external industries. In Malaysia, beyond mainstream political rhetoric it is possible that this objective is merely a myth. This research project examined three large institutions of higher learning in Malaysia - two public and one private - to gauge faculty productivity through regional collaboration and industrial linkage by academics in these institutions. Data gathered from questionnaires and selective interviews with research participants confirms that collaborations and linkages by Malaysian academics are few and far between and the target of the Malaysian government has not been realized, and is likely to be unachievable in the near future. Some of the reasons behind this failure are also highlighted by this current research effort.